2016
DOI: 10.1063/1.4965920
|View full text |Cite
|
Sign up to set email alerts
|

Improving the quality of proton beams via double targets driven by an intense circularly polarized laser pulse

Abstract: A new scheme is proposed to improve the quality of proton beams via ultra-intense laser pulse interacting with double plasma targets, which consist of a pre-target with relatively low density and a main target with high density. Both one- and two-dimensional Particle-in-Cell simulations show that, the using of an appropriate pre-target can help to obtain a much stronger longitudinal charge separation field in contrast to using only the main target. And proton beam with lower momentum divergence, better monochr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…This was possible only by the extreme contrast ratio (Danson et al, 2018) of the laser pulses as it was realized in retrospect only (Hora, 2016) by the blue Doppler shift of spectral lines (Sauerbrey, 1996;Zhang et al, 1998;Földes et al, 2000). The PIC computation with inclusion of dielectric response was difficult and succeeded only recently (Xu et al, 2016 to confirm the earlier hydrodynamic derivation of basic requirements for the operation of the reactor design of Figure 5.…”
Section: Design Of Laser Boron Fusion Reactormentioning
confidence: 90%
See 1 more Smart Citation
“…This was possible only by the extreme contrast ratio (Danson et al, 2018) of the laser pulses as it was realized in retrospect only (Hora, 2016) by the blue Doppler shift of spectral lines (Sauerbrey, 1996;Zhang et al, 1998;Földes et al, 2000). The PIC computation with inclusion of dielectric response was difficult and succeeded only recently (Xu et al, 2016 to confirm the earlier hydrodynamic derivation of basic requirements for the operation of the reactor design of Figure 5.…”
Section: Design Of Laser Boron Fusion Reactormentioning
confidence: 90%
“…These details are also of importance when the nonlinear force acceleration process in target layers is used for the generation of space charge neutral ion beams, with more than million times higher ion densities than the best classical accelerator can produce (Hora et al, 2017a(Hora et al, , 2007 for ion energies of few hundred MeV energy cancer treatment or for space craft propulsion (Hora et al, 2011;Lalousis et al, 2013;Hoffmann et al, 2018). Even nearly monoenergetic proton beams above GeV (Xu et al, 2016; It is shown in the 2nd and 3rd Sections that the ultrahigh plasma-block acceleration is the essential mechanism for the non-LTE process of the low-temperature ignition (Hora et al, 2015(Hora et al, , 2017a(Hora et al, , 2017b(Hora et al, , 2017c of the laser boron fusion for the new reactor design. This was possible only by the extreme contrast ratio (Danson et al, 2018) of the laser pulses as it was realized in retrospect only (Hora, 2016) by the blue Doppler shift of spectral lines (Sauerbrey, 1996;Zhang et al, 1998;Földes et al, 2000).…”
Section: Design Of Laser Boron Fusion Reactormentioning
confidence: 99%
“…This could be understood by using PIC computations with plasma densities below critical. The very difficult calculations at critical density were mastered only by JW Wang and his team recently (Xu et al, 2016Li et al, 2017;Hora et al, 2017c). As a test whether the PW-ps laser pulses have a sufficient contrast ratio may be that the light reflected from the irradiated target has to show a blue Doppler shift of spectral lines.…”
Section: Need For Very High Contrast Ratio Of Pw-ps Laser Pulsesmentioning
confidence: 99%
“…Under the irradiation of an intense laser pulse, the electrons of a microtube will be greatly heated due to collisionless absorption mechanisms [43]. Since the thickness of the microtube is on the order of the skin depth d s ≃ 40λ, these heated electrons will be largely blown away by the laser radiation [19,20]. While the ions are left due to their large mass-to-charge ratio as shown in Fig.…”
Section: Dynamics Of a Laser-irradiated Microtubementioning
confidence: 99%
“…For instance, the proton cut-off energy of 85 MeV with high particle numbers has been demonstrated in the recent experiment [18] via the target-normal sheath acceleration (TNSA), which is the most studied mechanism for laser-driven ion acceleration. In the double-target scheme proposed recently, it was found that the charge separation field in the main target can be greatly enhanced by introducing a relatively low-density pre-target [19][20][21]. As a result, the energy, quality and ion number of the accelerated ion beam can be all enhanced.…”
Section: Introductionmentioning
confidence: 99%